Mathematical representation ability: A systematic literature review - Jasmine Salsabila Lutfi; Dadang Juandi (Universitas Sarjanawiyata Tamansiswa, 2023)
One of the psychological aspects of students that encourage students' mathematical representation ability is self-confidence. The mathematical representation ability of each student is not the same, because of the student's ability to receive and process the information that the teacher has given during the lesson. Thus, the cognitive style also affects the ability of mathematical representation. This article is a systematic literature review (SLR) of 25 studies published until November 2022 with the help of the Publish or Perish (PoP) application with the Google Scholar database. This article aims to investigate: (a) the characteristics of the period, index, research approach, subject matter, and demographics of the participants in the identified articles, (b) learning methods that can improve students' mathematical representation and self-confidence abilities, and (c) the most frequently used cognitive style type. The results of research with SLR show that the Problem-Based Learning (PBL) learning model is effective and able to develop students' mathematical representation skills, and student self-confidence. Mathematical representation ability studies based on cognitive style mostly use Field Dependent (FD) and Field Independent (FI) types, and rarely use spatial and visualizer-verbalizer types. The results of this SLR can be useful for other researchers who are interested in researching this topic in the form of research gaps that can be done for the next research.